Evaluation of Carbonation Effects on Cement-Solidified Contaminated Soil Used in Road Subgrade - Yundong Zhou; Lingling Pan; Qiang Tang; Yu Zhang; Na Yang; Cong Lu (Advances in Materials Science and Engineering)
Cement solidification/stabilization is widely used towards contaminated soil since it has a low price and significant improvement for the structural capacity of soil. To increase the usage of the solidified matrix, cement-solidified contaminated soil was used as road subgrade material. In this study, carbonation effect that reflected the durability on strength characteristics of cement-solidified contaminated soil and the settlement of pavement were evaluated through experimental and numerical analysis, respectively. According to results, compressive strengths of specimens with 1% Pb(II) under carbonation and standard curing range from 0.44 MPa to 1.17 MPa and 0.14 MPa to 2.67 MPa, respectively. The relatively low strengths were attributed to immobilization of heavy metal, which consumed part of SiO2, Al2O3, and CaO components in the cement or kaolin and reduced the hydration and pozzolanic reaction materials. This phenomenon further decreased the strength of solidified soils. The carbonation depth of 1% Cu(II) or Zn(II) contaminated soils was 18 mm, which significantly increased with the increase of curing time and contamination concentration. Furthermore, the finite element calculation results showed that surface settlements decreased with the increase of modulus of subgrade and the distance away from the center. At the center, the pavement settlement was proportional to the level of traffic load.